THE IMPLEMENTATION OF LEAN STRATEGY TO ALLEVIATE OVERCROWDING IN EMERGENCY ROOM: NARRATIVE REVIEW - Yani Oryza; Jaslis Ilyas (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: Emergency Room (ER) of hospital worldwide undergoes significantly challenging problems; overcrowding patient leads to block the access, causes discomfort and increases demands to be served by medical personnel immediately. To overcome these problems, the ER needs to implement lean strategies. This study presents a narrative review aimed to identify whether there is a positive impact of the lean implementations in overcoming the overcrowded ER or not. Methods: This narrative review explores the current literature from an online database and highlights the lean strategies adopted by several ER to reduce overcrowding and delaying and to streamline patient flow. Literatures without data on waiting time, length of stay (LOS), and untreated patients leaving the ER, will be excluded from this review. The types of intervention were grouped into team triage, streaming, fast track, point-of-care test (POCT), and nurse-requested x-ray. Results: The evidence of lean intervention is beneficial in reducing patients’ waiting time and length of stay (LOS). Fast track reduces the length of waiting time, LOS, and the number of untreated patients by physician. Team triage consisting of appointed doctors and nurses also has a positive impact on shortening the waiting time. There is not enough evidence to suggest that streaming, POCT early in arrival, and x-rays by nurses can reduce waiting times and LOS. Conclusions: The implementations of lean strategy have a positive impact in shortening the waiting time and LOS, and help speed up the patients’ flow and access to other supporting units.